A study on the correlation potential of compaction characteristics and atterberg limits of selected lateritic soils - Adunoye, G.O; Ojo, A.A; Alasia, A.F; Olarewaju, M.O (International Journal of Physical Research, 2020)
The importance of soil compaction for civil engineering construction and application cannot be over-emphasised. To perform soil compaction, numerous number of samples are required, with considerable time and laborious laboratory activities. This has necessitated the need to find models for the prediction of compaction characteristics, using easily determined soil properties. This work therefore undertook a study of the correlation potential of compaction characteristics and Atterberg limits of soils, with a view to modelling compaction characteristics, using Atterberg limits. To achieve this aim, soil samples were obtained from selected locations within Obafemi Awolowo University campus, Ile-Ife, Nigeria. Preliminary, Atterberg limits and compaction tests were conducted on the soil samples, using standard procedure. Using Microsoft Excel and Xuruâ€™s Regression tool, the laboratory test results were used to develop relationships between compaction characteristics (optimum moisture content and maximum dry density) and Atterberg limits (liquid limit and plastic limit). Results showed that the natural moisture content of soil samples ranged between 4.97 % and 19.72 %; liquid limit ranged between 27 % and 68 %; plastic limit ranged between 18.92 % and 63.01 %; and plasticity index ranged between 0.94 % and 14.63 %. The optimum moisture content ranged between 6.7 % and 27 %, while the maximum dry density ranged between 1560 kN/m3 and 2260 kN/m3. The results of regression analysis showed that the combination of liquid limit and plastic limit has a strong correlation with optimum moisture content (R2 = 0.870); while the combination (of liquid limit and plastic limit) showed a weak correlation with maximum dry density (R2 = 0.150). The study concluded that liquid limit and plastic limit could be used to estimate the optimum moisture content of the soils, by applying the developed relationship/equation.Â Â